Architecture Design of E-Information System Marketplace with Method Enterprise Architecture Planning - Subhanjaya Angga Atmaja; Iwan Eka Putra; Ikhsan Akbar Muslim; Hendri Purnandi (Budapest International Research and Critics University, 2021)
Utilization of a technology indispensable information on SMEs because they develop information technology will be more complete and would affect ongoing business developments. At this time, not a few developments and development of information system technology have failed, this is because it is not following the goals and needs of these business people. One technique that can be used to build/develop information system technology is the existence of Enterprise Architecture Planning, where this technique is a technique used to approach data quality planning by looking at the needs of the SME business in Enterprise Architecture Planning will be explained about applications, data architecture, technology and a roadmap for the implementation plan of the architecture. SMEs cannot be separated from the need that can define business needs and even information architecture so that the direction of business development policy strategies can be well planned. Information technology architecture modeling in SMEs, including application definition, data architecture, technology, and implementation plan mapping. The process when defining information technology architecture is reviewed and refers to processes that are common in the business of implementing E-Marketplace applications, especially in SMEs. The results of the research will produce a mapping of implementation plans that can be used as a reference in the development of an application to support the business functions of SMEs.